Marine and Soil Derived Natural Products: A New Source of Novel Cardiovascular Protective Agents Targeting the Endothelin System - Planes, Nadir; Caballero-George, Catherina (Planta Medica, 2015)
Inhibition of the endothelin system is a recognized therapeutic approach for treating complex cardiovascular diseases. The search for natural inhibitors of the endothelin system has focused mainly on land, with recent, emerging data suggesting the underestimated potential of marine microorganisms for producing leads with cardioprotective potential. The present work reviews natural products identified as inhibitors of the endothelin system, their origin, their mechanism of action, and their ecological significance.
Keywords: endothelin; hypertension; cardiovascular; marine natural products; microorganisms; ecology